The role of TEKUN Nasional in financing micro enterprise sector in Malaysia - Mohd Shariff, Mohd Noor; Nawai, Norhaziah (UUM Press, 2012)
In line with the government’s intention to become high income nation by 2020, SME development has become national priority to achieve Vision 2020. The government aims to bring SME, including micro enterprises into the economic mainstream to become an important engine in Malaysia’s economic growth.Therefore, many programs were implemented such as 1Azam program which builds up the capabilities of the poor and creates jobs for them in varied industries including agricultural and agro-based and small-business plus self-employment to create opportunities for low-income households to earn income independently.The government allocates a lot of funds such as Economic Stimulus Package, Economic Planning Unit (EPU) funds and SME development scheme.The government channels the funds through Micro Finance Institutions namely Amanah Ikhtiar Malaysia, TEKUN Nasional, MARA, PUNB and selected banks that offer microfinancing.This monograph discusses the Intermediary Model in financing micro enterprise sector in Malaysia and analyzing as well as determining the factors affecting repayment performance in microfinance programs in Malaysia.